Early Cinema in Asia - Deocampo, Nick (Book collections on Project MUSE., 2017)
"Early Cinema in Asia explores how cinema became a popular medium in the world's largest and most diverse continent. Beginning with the end of Asia's colonial period in the 19th century, contributors to this volume document the struggle by pioneering figures to introduce the medium of film to the vast continent, overcoming geographic, technological, and cultural difficulties. As an early form of globalization, film's arrival and phenomenal growth throughout various Asian countries penetrated not only colonial territories but also captivated collective states of imagination. With the coming of the 20th century, the medium that began as mere entertainment became a means for communicating many of the cultural identities of the region's ethnic nationalities, as they turned their favorite pastime into an expression of their cherished national cultures. Covering diverse locations, including China, India, Japan, Philippines, Malaysia, Thailand, Iran, and the countries of the Pacific Islands, contributors to this volume reveal the story of early cinema in Asia, helping us to understand the first seeds of a medium that has since grown deep roots in the region"--